2014
DOI: 10.3906/bot-1303-29
|View full text |Cite
|
Sign up to set email alerts
|

Lichenized and lichenicolous fungi of Gevne Valley (Konya, Antalya)

Abstract: it is still far from being fully satisfactory. The lichenicolous fungi of Turkey have started to receive more attention during the last 5 years. Halıcı (2008a) published a key to the 117 known taxa of lichenicolous Ascomycota (including mitosporic fungi) of Turkey; since that publication, studies on lichenicolous fungi have continued (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The total number of ascomycetous fungi recognized as occurring in Turkey increased to 217 with the recent study by Uzun et al (2014). Lichenized and lichenicolous fungi of Gevne valley (Konya, Antalya) were documented by Kocakaya et al (2014). Solak et al (2014) identified 136 taxa belonging to 40 families in Antalya Province, and 3 of them (Cortinarius subferrugineus (Batsch) Fr., Entoloma vernum S. Lundell, and Inocybe piceae Stangl & Schwöbel) were new records for Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of ascomycetous fungi recognized as occurring in Turkey increased to 217 with the recent study by Uzun et al (2014). Lichenized and lichenicolous fungi of Gevne valley (Konya, Antalya) were documented by Kocakaya et al (2014). Solak et al (2014) identified 136 taxa belonging to 40 families in Antalya Province, and 3 of them (Cortinarius subferrugineus (Batsch) Fr., Entoloma vernum S. Lundell, and Inocybe piceae Stangl & Schwöbel) were new records for Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…This Athallia is usually recognizable in the field by its tiny areolate to granular yellow-orange thallus, usually spread on thin crusts of other lichens or squeezed between areoles of thicker crusts. Athallia areoles are smaller To our understanding, A nesodes includes two traditionally recognized taxa: (1) What has been called (incorrectly) "Caloplaca inconnexa" by some authors, usually growing on calcareous substrata and lichenicolous on various lichen crusts, especially Acarospora cervina (Figure 3), Aspicilia calcarea, and Lecanora saxicola (Vondrák et al, 2007;Halıcı and Aksoy, 2009;Urbanavichus and Ismailov, 2013;Vondrák and Wirth, 2013;Kocakaya et al, 2014); and (2) Caloplaca inconnexa var. nesodes, occurring on coastal or inland siliceous rocks and lichenicolous on Aspicilia spp.…”
Section: New Combinationsmentioning
confidence: 99%
“…Studies on lichens and lichenicol fungi in our country increased in the late 20th and early 21st centuries. These studies are mostly floristic studies covering certain regions (Aslan et al 2002;Yazıcı et al 2008;Öztürk & Güvenç 2010;Çobanoğlu et al 2013;Kocakaya et al 2014;Koç et al 2017;Yavuz & Çobanoğlu 2018;Oran 2021). As a result of increasing lichen studies in recent years, more than 100 lichen and lichenicolous fungus species have been identified in our country by researchers (John et al 2020).…”
Section: Introductionmentioning
confidence: 99%